2018
DOI: 10.18203/2320-1770.ijrcog20184230
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of polycystic ovarian syndrome among adolescent girls: a prospective study

Abstract: Background: PCOS is a complex   endocrine   disorder which is most common in women of reproductive age. PCOS may first present in adolescence, but the incidence of PCOS in adolescence is not known, as diagnostic criteria for PCOS in the adolescent age-group is still not defined, PCOS symptoms tend to overlap with normal pubertal changes making the diagnosis even more challenging. The objective is to study prevalence and symptomatology of polycystic ovary syndrome (PCOS) in adolescent girls.Methods: Prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 6 publications
5
24
0
2
Order By: Relevance
“…Further 58.9% patients of PCOS were presented with complaints of hirsutism in the present study. Again, the percentage is comparable to studies conducted by Anjali C et al, Sinha A et al, Himabindu et al, Lakshmi KS et al and Sunita J et al 13,[15][16][17][18] Who observed that 64.2%, 21%, 48%, 47.8% and 44.16% patients of PCOS presented with complaints of hirsutism respectively. As this study's being hospital based could be the possible explanation for the high prevalence of hirsutism observed.…”
Section: Distribution According To the Clinical Presentationsupporting
confidence: 84%
See 1 more Smart Citation
“…Further 58.9% patients of PCOS were presented with complaints of hirsutism in the present study. Again, the percentage is comparable to studies conducted by Anjali C et al, Sinha A et al, Himabindu et al, Lakshmi KS et al and Sunita J et al 13,[15][16][17][18] Who observed that 64.2%, 21%, 48%, 47.8% and 44.16% patients of PCOS presented with complaints of hirsutism respectively. As this study's being hospital based could be the possible explanation for the high prevalence of hirsutism observed.…”
Section: Distribution According To the Clinical Presentationsupporting
confidence: 84%
“…The results are similar to studies conducted by Choudhary A et al, Sinha A et al, Himabindu et al, wherein significantly high percentage 68%, 71% and 87% of PCOS patients presented with oligomenorrhea. 13,15,16 This supports to conclude that oligomenorrhea among women of reproductive age can be largely explained by PCOS.…”
Section: Distribution According To the Clinical Presentationsupporting
confidence: 69%
“…In Singh A et al, study incidence of mood changes was 14%. 11 Many girls had a combination of symptoms present, same results seen in study done by Pathak G et al 12 Most common being menstrual irregularities and acne or oily skin suggestive of androgenic activity.…”
Section: Discussionsupporting
confidence: 61%
“…2 Studi baru menujukkan bahwa SOPK mempengaruhi 2,2-20% dari wanita dengan usia reproduksi. 3 Suatu studi menunjukkan bahwa prevalensi SOPK lebih tinggi pada wanita dengan berat badan berlebih, obesitas, dan hingga 30% wanita yang memiliki IMT >30 kg/m2 memenuhi kriteria diagnostik SOPK. 4 Berat badan berlebih berpengaruh terhadap subfertilitas pada seorang wanita dan dapat memengaruhi organ reproduksi yang menyebabkan menstruasi tidak teratur, subfertilitas, Sindrom Ovarium Polikistik (SOPK), kanker rahim, endometrium, payudara, dan serviks.…”
Section: Pendahuluanunclassified
“…Populasi 3 Hasil analisis energi dan makronutrien dari 150 sampel remaja yang berusia 15-19 tahun, menunjukkan bahwa rata-rata sampel dengan intake kalori, konsumsi karbohidrat dan lemak yang berlebih, konsumsi protein yang cukup, serta konsumsi serat yang kurang. Hasil penelitian ini sesuai dengan penelitian yang dilakukan Kurdanti et al, (2015) yang menyatakan bahwa dari 144 sampel yang diteliti, sebanyak 84,7% sampel dengan intake kalori yang berlebih, 66,7% dengan konsumsi karbohidrat yang berlebih, 58,3% dengan konsumsi protein yang cukup, 56,9% dengan konsumsi lemak yang berlebih, dan 59,7% dengan konsumsi serat yang kurang.…”
Section: Metodeunclassified